Clinical Outcomes of Transcranial and Endoscopic Endonasal Surgery for Craniopharyngiomas: A Single-Institution Experience - Nie, Chuansheng; Ye, Youfan; Wu, Jingnan; Zhao, Hongyang; Jiang, Xiaobing; Wang, Haijun (Frontiers in Oncology, 2022)
Objective Craniopharyngioma has always been a challenge for the neurosurgeon, and there is no consensus on optimal treatment. The objective of this study was to compare surgical outcomes and complications between transcranial surgery (TCS) and endoscopic endonasal surgery (EES) of craniopharyngiomas. Methods A retrospective review of patients who underwent craniopharyngioma resection at Wuhan Union Hospital between January 2010 and December 2019 was performed. A total of 273 patients were enrolled in this retrospective study. All patients were analyzed with surgical effects, endocrinologic outcomes, complications, and follow-up results. Results A total of 185 patients underwent TCS and 88 underwent EES. There were no significant differences in patient demographic data, preoperative symptoms, and tumor characteristics between the two groups. The mean follow-up was 30.5 months (range 8–51 months). The EES group had a greater gross total resection (GTR) rate (89.8% EES vs. 77.3% TCS, p < 0.05) and lower rate of hypopituitarism (53.4% EES vs. 68.1% TCS, p < 0.05) and diabetes insipidus (DI) (51.1% EES vs. 72.4% TCS, p < 0.05). More postoperative cerebrospinal fluid (CSF) leaks occurred in the EES group (4.5% EES vs. 0% TCS, p < 0.05). More patients in the EES group with preoperative visual deficits experienced improvement after surgery (74.5% EES vs. 56.3% TCS, p < 0.05). There were statistical differences in the recurrence rates (12.5% EES vs. 23.8% TCS, p < 0.05) between the 2 groups. Conclusion These data support the view that EES is a safe and effective minimally invasive surgery compared to TCS. Compared to TCS, EES has fewer surgical complications and a lower recurrence rate.